Choosing the probe radiation wavelengths for noninvasive monitoring of haemoglobin in blood - Igor L. Davydkin (Journal of Biomedical Photonics & Engineering, 2016)
The goal of our study was to estimate the accuracy of measuring the blood haemoglobin concentration by means of the pulse CO-oximetry, depending on the probe radiation wavelength. Revealing the combinations of wavelengths, optimal for minimising the measurement error, will allow the formulation of requirements to the instruments for noninvasive assessment of haemoglobin concentration, applicable in wide clinical practice. To solve this problem, we examined a group of haematological patients in the Haematology Department of the Samara State Medical University Clinic with the aim to compare the results obtained using the experimental multiwave system for noninvasive haemoglobin concentration assessment and the results of the clinical blood analysis.